Building an Entrepreneurship Development Model for Millennial Farmers Human Resources - Setiawan, Heri Cahyo Agus; Prasetya, Agus; Ilham, Ilham; Fatimah, Nuzulul; Latukismo, Tatag Herbayu (Sharia Agribusiness Journal, 2023)
In industry 4.0, agricultural human resources, especially the millennial generation, are required to have an entrepreneurial spirit and technological capabilities in carrying out entrepreneurial activities in the agricultural sector. Not many studies that discuss farmers human resources millenial in Indonesia have been studied seriously, especially educational institutions that deal with the entrepreneurial agricultural sector (Setiawan, et.al, 2023). Sustainable development of agricultural human resources requires the development of farmers' own entrepreneurship. So it requires support from all parties, especially the world of education, which has a vision and mission and an orientation towards developing agricultural human resources. In Indonesia, one of the educational programs that educates agricultural human resources and millennial farmers has begun to grow, one of which is the Agripreneur Academy. This research aims to explore what is the human resource development model for millennial farmers with an entrepreneurial character? The research method used was qualitative by conducting in-depth interviews with millennial farmer informants who were participants in the agripreneur academy program. For validation, we also conducted a group discussion forum with informants from the management of the Agripreneur Academy, academics from university and agricultural figures from associations. This research produces the following results: (1) agripreneur academic institutions play a role in building the entrepreneurial mindset of millennial farmers' human resources that farmers must be able to become entrepreneurs in the agricultural sector; (2) the character of the formation of farmers with an innovative spirit, from being limited to traditional farmers transforming into millennial entrepreneurial farmers who are market-oriented and utilize technology in marketing the agricultural food products that are being developed.  Keywords: human resources; millennial farmer; agripreneur; entrepreneurship  ABSTRAK Dalam industri 4.0, sumber daya manusia pertanian khususnya generasi milenial dituntut memiliki jiwa wirausaha dan kemampuan teknologi dalam menjalankan kegiatan wirausaha di sektor pertanian. Belum banyak penelitian yang membahas tentang sumber daya manusia petani milenial di Indonesia yang dikaji secara serius, khususnya lembaga pendidikan yang bergerak di bidang wirausaha sektor pertanian (Setiawan, et.al, 2023). Pembangunan sumber daya manusia pertanian yang berkelanjutan memerlukan pengembangan kewirausahaan petani itu sendiri. Sehingga memerlukan dukungan semua pihak khususnya dunia pendidikan yang memiliki visi misi dan orientasi pada pengembangan sumber daya manusia pertanian. Di Indonesia, salah satu program pendidikan yang mendidik SDM pertanian dan petani milenial sudah mulai tumbuh, salah satunya adalah Agripreneur Academy. Penelitian ini bertujuan untuk mengeksplorasi bagaimana model pengembangan sumber daya manusia petani milenial yang berkarakter wirausaha? Metode penelitian yang digunakan adalah kualitatif dengan melakukan wawancara mendalam terhadap informan petani milenial peserta program agripreneur academy. Untuk validasi, kami juga melakukan forum diskusi kelompok dengan narasumber dari pimpinan Agripreneur Academy, akademisi dari universitas dan tokoh pertanian dari asosiasi. Penelitian ini menghasilkan hasil sebagai berikut: (1) institusi akademik agripreneur berperan dalam membangun pola pikir kewirausahaan sumber daya manusia petani milenial bahwa petani harus mampu menjadi wirausaha di bidang pertanian; (2) karakter terbentuknya petani yang berjiwa inovatif, dari yang semula hanya sebatas petani tradisional bertransformasi menjadi petani wirausaha milenial yang berorientasi pasar dan memanfaatkan teknologi dalam memasarkan produk pangan pertanian yang dikembangkan.  Kata Kunci:     sumber daya manusia; petani milenial; agripreneur; kewirausahaan